Maximizing Impact: Unleashing Employee Performance through Transformational Leadership, Organizational Commitment, and Work Engagement - Sathyanarayana S, Neha Mahesh Inamdar, Sreeja S, Rachna Jain, Shikha Sharma, Satuluri Padma (Journal of Informatics Education and Research, 2024)
Throughout the course of this in-depth study, the complex linkages that exist between transformational leadership, organizational commitment, job engagement, and employee performance are thoroughly investigated. The research sheds light on the intricate connections that exist between these essential components by utilizing a substantial sample size of 185 individuals who were drawn from manufacturing businesses in India. The purpose of this study is to provide a comprehensive understanding of how transformational leadership styles, organizational commitment levels, and work engagement all contribute synergistically to elevate employee performance. This is because all of these factors are positively related to employee performance. The study will accomplish this by utilizing both quantitative analysis and qualitative insights. In terms of all the independent variables on the dependent variable, the regression coefficient is 0.77. The empirical findings, which were derived from a sample that was carefully selected, offer practical implications for firms that are looking to maximize the potential of their personnel. The purpose of this research is to shed light on the tactics that can promote organizational effectiveness and foster a culture of sustained high performance. This is accomplished by embracing ideas from both the leadership and employee perspectives. Not only do the findings make a contribution to the scholarly discourse on leadership and the dynamics of the workplace, but they also offer advice that can be put into practice by professionals who are looking to develop a work environment that is both thriving and productive.